PENGARUH JUS TOMAT TERHADAP PENURUNAN GULA DARAH SEWAKTU PADA PENDERITA DIABTES MELLITUS TIPE 2 DI DUSUN GEMANTAR KECAMATAN SELOGIRI KABUPATEN WONOGIRI - Nugroho, Yohanes Wahyu (Akademi Keperawatan Giri Satria Husada Wonogiri, 2021)
Diabetes mellitus (DM) type 2 is a disease of excess blood sugar levels in the body resulting in increased blood sugar levels due to lack of insulin. DM type 2 is a chronic disease, not infrequently patients with DM depends on drugs throughout life. Drug consumption brings economic impact besides side effects of course. Therefore it is necessary alternative treatment in preventing the occurrence of DM type 2 disease by using vegetables and fruits. Tomato juice is a drink that is associated with the decrease of blood glucose levels. This study were designed to prove the effect of tomato juice on blood glucoseÂ levels in Patients Diabetes Mellitus type 2. The study design used was quasy- experimetal by using the draft of pre-test post-test control group design. The populations of DM type 2 patient were in the village of Gemantar, Wonogiri. the total sample of them were 38 respondents. The sampling tehnique used was purposive sampling. Statistical analysis used was paired t-test and independent t-test, with the significance of p <0.05 which means that H0 is rejected. The statistical test result of treatment group showed that there was effect of tomato juice to decrease before-meal blood glucose level. with the value of p = 0.000, while the statistical results of Unpaired t-test for comparison between two groups obtained blood glucose level (GDS) of p value <0.05 which means significant decrease of blood glucose level (GDS). The conclusion of this study is the statistical test showed there are significant differences on blood glucose levels decrease before and after being given tomato juice. Objective : To find out the effectiveness significant results that tomato juice can be an alternative choice in decreasing blood sugar levels (GDS) in diabetics mellitus type 2.